Zenit. (Zagreb, 1921)
Zenit (Zenith) was the most important avant-garde magazine published in the former Yugoslavia and one of the most significant publications of the broader European avant-garde movement of the early 20th century. It was launched in February 1921 by the artist Ljubomir Micić (1895-1971) and published monthly in Zagreb and Belgrade until December 1926, when it was banned by the authorities. A total of 43 issues were published, as well as one poster, “Zenitismus,” and one issue of a daily Zenit newspaper dated September 23, 1922. “Zenitism” was an avant-garde movement born around the magazine. The Zenitist Manifesto of June 1921 proclaimed humanist and anti-war ideals, and called for the creation of a new and united Europe. Besides Micić, noteworthy contributors to Zenit included Miloš Crnjanski, Dušan Matić, Stanislav Vinaver, Pablo Picasso, Alexander Blok, Jaroslav Seifert, Wassily Kandinsky, Vladimir Tatlin, Kazimir Malevich, Tommaso Marinetti, Marc Chagall, Ilya Ehrenburg, and many others. The complete run of Zenit presented here is from the special collections of the National Library of Serbia, and is part of the Micić’s legacy to the library (https://www.wdl.org/en/item/2342/)
Fotokopies en CD-Rom
Online: World digital Library: https://www.wdl.org/en/item/2342
International Dada Archive: https://dada.lib.uiowa.edu/collections/show/35
Bespreking uit Nationale Bibliotheek van Servië: https://www.wdl.org/en/curator-video/15
Tijdschriften
Keywords: avant-garde.; Europa